A Review on Empirical Correlations for Jet/Spray Trajectory of Liquid Jet in Uniform Cross Flow. (December 2015) - No, Soo-Young
The empirical correlations for the prediction of jet/spray penetration of liquid jet in subsonic uniform crossflow are reviewed in this study. Considerable number of empirical correlations had been proposed by many investigators. It has generally known that the jet/spray trajectory of a liquid jet in a cross-flow is a function of the liquid to air momentum flux ratio and the normalized distance in the airstream direction from the injector. However, several researchers incorporated the Weber number, liquid-to-water or air viscosity ratio, pressure ratio or Reynolds number, temperature ratio in the empirical correlations. Two different classification methods of correlations, i.e. classification based on mathematic functional form and classification based on flow regime, are introduced in this study. The one classification of existing correlations based on functional form includes correlations in a power-law, logarithmic, and exponential forms, respectively. The other classification of previous correlations based on flow regime includes one, two and three regime, correlations. Correlations in a power-law functional form can be further divided into three groups such as momentum flux ratio, Weber number and other parameters forms. Correlations in logarithmic functional form can be also grouped as momentum flux ratio and Weber number forms. Most of the evaluation studies reported the significant discrepancies of predicted values by the existing correlations. The possible reasons for discrepancies will be summarized as measurement technique, assumptions made in defining terms in the liquid to air momentum flux ratio, difficulties in defining the boundaries of the liquid jets, turbulence level in the core and boundary layer of incoming jet and gas flows, nozzle/injector geometry and its position in the crossflow. However, it can be found from the several evaluation studies that the power-law functional form with momentum flux ratio and two regimes correlations provided relatively the best fit to experimental data.